The ad hoc cello quartet: Gal Faganel, Heidi Mausbach, Barbara Thiem, Charlie Tucker - Colorado State University. Department of Music, producers (managers) (Colorado State University. Libraries, 2011)
Program mis-dated February 5, 2011.
Gal Faganel, Heidi Mausbach, Barbara Thiem, Charlie Tucker: The ad hoc cello quartet
Special guests: The Ad Hoc Cello Quartet
Keywords: Ad Hoc Cello Quartet (Organ Recital Hall, 2011); Gal Faganel, Heidi Mausbach, Barbara Thiem, Charlie Tucker (Organ Recital Hall, 2011)